Biomechanical Comparison of 2 Double Plating Methods in a Coronal Fracture Model of Bicondylar Tibial Plateau Fractures. Issue 4 (April 2022) - Samsami, Shabnam; Pätzold, Robert; Neuy, Tim; Greinwald, Markus; Müller, Peter E.; Chevalier, Yan; Püschel, Klaus; Augat, Peter
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: Because management of bicondylar tibial plateau fractures are complicated even for expert surgeons, with using a coronal fracture model, we aimed to compare 2 kinds of double locked plating techniques that consisted of the lateral locking plate and the medial locking plate inserted medial anteriorly (MA-ly) or medial posteriorly (MP-ly). Methods: Fourteen fresh-frozen tibias stabilized with the MA or MP methods were allocated into 2 groups with similar bone mineral density values. Implanted samples were tested under incremental fatigue loading conditions using a customized load applicator. An optical motion tracking system was used to assess relative displacements and rotations of fracture fragments during loading. Static and dynamic global stiffness, failure load, failure cycles, as well as movements of fracture fragments were measured. Results: There were no significant differences between the 2 fixation methods regarding global stiffness, failure load, or failure cycles ( P = 0.67–0.98, depending on the parameter). The kinematic evaluations, however, revealed that different positions of the medial locking plates altered the directions of movements for the medial-anterior or medial-posterior fracture segments. Conclusions: The mechanical stability of tibia-implant constructs fixed with the double plating methods was not remarkably affected by the location of the medial locking plate. Depending on clinical conditions and surgeons' preferences, bicondylar tibial plateau fractures can be managed with either MA or MP methods.